A prospective observational study of factors affecting the outcome of intestinal anastomosis - Hareesh H D; Preethi S.P; Champa B V; Anusha KM (International Journal of Health and Clinical Research, 2021)
Introduction: Intestines form a major part of human digestive system. Both in terms of length as well as surface area, the small and large intestines constitute about 90% of the digestive system. They play a major role in absorption of nutrients, water and other micro nutrients. Thus they play a major role in growth and proper functioning of the human body. Any pathological condition of the bowel leads to disturbance in the homeostasis of the human body. Materials and Methods: A prospective study was conducted from March 2019 to February 2020 at Department of General Surgery, Shivamogga Institute of Medical Sciences, Shivamogga, India. All patients undergoing hand-sewn gastro-intestinal anastomosis electively as well as those as an emergency procedure were included in this study. The total number of cases studied were 160. Statistical analysis was done using SPSS version 20.0 and p values were calculated using Chi-square test and unpaired t test. Results: Over a period of 1 year, 160 patients who underwent hand-sewn intestinal anastomosis were included in this study, of which 88 were done electively, and 72 were done on emergency basis. All the patients had only one anastomosis performed. The mean age of the patients operated upon in the present study was 38.66±13.96 years (ranging from 18-72 years) which included 120 male patients (75%) and 40 female patients (25%) (Table 1). The most common diagnosis was ileostomy reversal (51%) followed by Ileal perforations (24%) secondary to various causes and small and large bowel obstructions (15%) while the most frequent site of anastomosis was ileo-ileal (77.5%) followed by ileo-transverse (16%). Conclusion: This study identified and assessed the various risk factors associated with anastomotic leaks and found age, sex, anaemia, sepsis, hypoproteinemia, hypoalbuminemia, increased operative-time to be significant and we concluded that controlling these factors will help in minimizing the chances of anastomotic dehiscence.